EMPIRICAL STUDY ON THE OPERATIONAL CHALLENGES FACED BY ASSESSEE UNDER THE FACELESS ASSESSMENT SCHEME (FAS) IN INDIA - Rai, Archie; M. S Suganthiya (International Journal of Research -GRANTHAALAYAH, 2025)
This study presents an empirical evaluation of the practical difficulties encountered by taxpayers and their representatives during the execution of the Faceless Assessment Scheme (FAS) in the Indian Direct Tax framework. The central hypothesis explored is that the removal of physical interaction, while promoting transparency, inadvertently creates significant procedural friction. By administering a structured quantitative survey, this study collected primary evidence regarding two key areas of operational distress: the exorbitant volume and technical complexity of digital document submissions and the resulting ambiguity created by the lack of verbal clarification for complex financial matters. The resultant data indicate a strong correlation between these operational shortcomings and a noticeable spike in the administrative burden on the assessee, often culminating in contested assessment orders due to mutual misunderstanding. This analysis concludes by offering actionable, evidence-based recommendations for policy modifications aimed at restoring equilibrium between efficient administration and the fundamental right of the assessee to provide clear, effective explanations